Meningkatkan Kemampuan Pengurangan Dua Bilangan Maksimal 50 Melalui Media Papan Hitung bagi Peserta Didik Disabilitas Rungu (Action Resecarch Kelas VI di SLB N 1 Panti) - Hanum, Taskiya; Zulmiyetri, Zulmiyetri; Efrina, Elsa; Triswandari, Retno (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to improve the ability to subtract two numbers in a series downwards with the borrowing technique through the use of counting board media for deaf students in grade VI at SLB N 1 Panti. The type of research used is Classroom Action Research (CAR). The subjects in this study were two deaf students in grade VI at SLB N 1 Panti. The study was conducted in two cycles, where each cycle consisted of four meetings covering the planning, implementation, observation, and reflection stages systematically. Data collection techniques were carried out through observation, documentation, and testing. Based on the results of the study, it was found that the initial ability of students in subtracting using the borrowing technique was at 0% for RR and 0% for PA. In cycle I there was an increase, namely RR reaching 50% and PA 60%. Furthermore, in cycle II, students' abilities increased significantly to RR 95% and PA 100%. These results indicate that the use of counting board media is effective in improving the ability to subtract two numbers with the borrowing technique in deaf students.